Liquid-state quantitative SERS analyzer on self-ordered metal liquid-like plasmonic arrays - Li Tian (Nature Portfolio, 2018)
The design and application of a liquid interfacial plasmonic platform promises for practical applications of surface-enhanced Raman scattering (SERS). Here, the authors report a reversible chloroform/water encasing strategy to self-assemble metal liquid-like 3D gold nanorod arrays with attractive SERS capability.